Nursing care for heart failure patients and related factors at Hanoi Heart Hospital in 2024 - Nguyen, Thi Thu Phuong; Vu, Quynh Nga; Bach, Thi Hoa; Le, Thi Thanh Binh; Pham, Thi Hong Thi (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Objective: To assess the nursing care quality and some factors related to the outcome of care for hospitalized heart failure patients at Hanoi Heart Hospital in 2024.Method: We performed a cross-sectional study evaluating 21 routine nursing care activities for the level of completion on three days: day 1, day 3, and the day of discharge. We also identified the relevant factors to the patient care outcome. The data was collected from medical records and patient interviews.Results: Among the total of 156 hospitalized heart failure patients participating in the study, 83.3% of patients received good nursing care at the hospital, while only 16.7% of heart failure patients did not receive adequate nursing care. Factors related to the outcome of patient care include: Age group, gender, socioeconomic status, number of hospitalizations per year, disease duration, and patient satisfaction. (p < 0.05).Conclusion: Proper nursing care for hospitalized.